Feasibility of implementing Integrated Management of Childhood Illnesses through Mobile Technology. (30th September 2020) - Dharma, V K; Abdullah, S; Khan, A J; Munir, M; Siddiqi, D A; Shah, M T; Habib, A; Chandir, S
Abstract: Background: The Integrated Management of Childhood Illnesses (IMCI) strategy was launched by WHO and partners in 1995 to reduce child mortality by enhancing frontline health workers' (FHWs) ability to diagnose and manage childhood illnesses, and strengthen overall health systems. However, although IMCI is associated with decreased child mortality, numerous studies have shown its impact has been limited due to persistent barriers to implementation. Methods: We developed a digitized version of IMCI (eIMCI) using Android technology to overcome implementation problems, including poor protocol compliance, lengthy trainings, paper-based data collection, and gaps in the referral system. The feasibility and efficacy of eIMCI was assessed through a mixed-methods pilot study encompassing baseline and end-line surveys, interviews, and Focus Group Discussions, in a low-resource rural district of Punjab, Pakistan. During the 8 weeks of deployment, a total of 1, 978 children were enrolled in the eIMCI application by 10 participating FHWs, and 47 electronic referrals were generated. Results: Preliminary outcomes showed reduced disease occurrence (for example, diarrhea decreased from 48% at baseline to 29% at endline), increased adherence to IMCI protocol, and strengthened health system linkages (facility referrals increased from 5% at baseline to 45% at endline). FHWs reported enhanced performance, as well as an improved community response to their services. Discussion: Indicating the feasibility and efficacy of eIMCI deployment in a low-resource setting, evidence from the pilot demonstrates the benefit of digitizing the IMCI protocol. eIMCI is a digital health solution with the potential to significantly reduce child mortality and improve service delivery and performance of FHWs. Key messages: eIMCI is a feasible solution for the implementation of IMCI strategy in developing countries and demonstrates increased compliance and enhanced performance by the frontline health workers. Implementation of eIMCI can result in a significant reduction in child morbidity and mortality via timely referrals of patients and reduced disease occurrence.